Dental Veneers - Alyari, Melika; Zurabiani, Nuca (Caucasus Journal of Health Sciences and Public Health, 2020)
Increasing high tendency of the people in have better smile and whiter teeth make the dentists to enhance their ability to create the Hollywood smile. Veneers are fingernail-like shells that are custom fit and permanently bonded to the fronts of the teeth. They are made of thin layers of either porcelain or a strong composite resin. Veneers can be effective treatment for the bad shaped teeth,cracked, discolored and shorted teeth.there is also some condition which using veneers are not recommended such as tooth with decay, periodontal disease, clenching and bruxism. mainly veneers have two types: composite resin veneer and porcelain veneers. The composite resin veneer is actually fabricated right on tooth by dentist and a porcelain veneer is made at a dental lab out of ceramic porcelain. Veneer composites have spongy form structure that’s why they may have changing colors in case of using too much for example coffee or red wine and… which is mostly depends on the patient’s diet. But in case of taking care of these veneers they can stay about 4-8 years. One of the benefits of usage of the composite is they are reversible that means the dentist can remove them from the teeth or completely change them in a short time. porcelain veneers are one of the most beautiful restorations available in cosmetic dentistry. Depending on the initial condition of the teeth, more or less of the teeth structure will have to be removed in order to accommodate the veneers. This is done by trimming the enamel from the front and biting edge of your teeth. A porcelain veneer is usually about 0.5 to 0.7 millimeters in thickness. Once bonded to healthy tooth structure it becomes very strong. Emax veneers are primarily made of pressed ceramic, which makes them highly durable. Moreover, these come in thin layers, and this prevents the need for drilling teeth.this is the most impressive feature of this type of veneer since teeth are preserved, unlike with conventional veneers To know whether composite or porcelain veneers are right for patient is to decide what factors are most important to him: aesthetic preference, durability, cost, and time involved. Composite veneers are best bet if efficiency and cost-effective solution is needed. If having a natural look is more